VD_FINDINFO PC 12/22 - 25/2023 vom 14. Juni 2023 - VD Tribunal cantonal (2023)
ERREUR DE CALCUL, ADMISSION PARTIELLE, RESTITUTIONEN GÉNÉRAL | 10 LPC, 11 al. 1 LPC, 9 al. 1 LPC, 25 LPGA, 53 al. 1 LPGA, 15c al. 3 OPC-AVS/AI, 24 OPC-AVS/AI, 25 OPC-AVS/AI